Dino duckling - Murray, Alison (Orchard Books, 2018)
Dino Duckling can dive, swim and fish just like his duckling brothers and sisters. But when the time comes for the family fly south for the winter... can Dino Duckling ever truly belong?
"A funny and heart-warming celebration of difference, inspired by Hans Christian Andersen's The Ugly Duckling" -- Back cover
First published in Great Britain in 2017 by The Watts Publishing Group
Keywords: Andersen, Hans Christian -- 1805-1875 -- Den grimme aelling; Bearbeitung; Dinosaurs / Juvenile fiction; Ducks / Juvenile fiction; Individual differences / Juvenile fiction; Belonging (Social psychology) / Juvenile fiction; Belonging (Social psychology); Dinosaurs; Ducks; Individual differences; Picture books; Fiction; Juvenile works; Children's stories / Pictorial works; Bilderbuch